2012
DOI: 10.1038/cgt.2012.33
|View full text |Cite
|
Sign up to set email alerts
|

The role of natural killer cells in combinatorial anti-cancer therapy using Sindbis viral vectors and irinotecan

Abstract: Oncolytic viruses (OVs) have shown great anti-cancer potential in animal models, but only modest success in early clinical trials. A better understanding of the mechanisms underlining OV efficacy is needed to resolve this discrepancy. In the clinic, OV therapy will likely be combined with traditional chemotherapy, underscoring the need to also evaluate the interactions between these therapeutic modalities. Here we show that combining Sindbis viral vector therapy with the topoisomerase inhibitor irinotecan (CPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…Irinotecan has been shown to inhibit HSV-1 viral replication and lytic oncolysis in colon cancer cell lines 164. In contrast, other groups show synergy with OVs/irinotecan, including HSV-1 encoding CYP2B1,127 reovirus,128 and Sindbis virus 126. However, only the study on Sindbis virus looked at immune components in irinotecan synergy, concluding that natural killer cells are essential for the process 126…”
Section: Combining Chemotherapeutic Drugs With Ov Therapymentioning
confidence: 99%
“…Irinotecan has been shown to inhibit HSV-1 viral replication and lytic oncolysis in colon cancer cell lines 164. In contrast, other groups show synergy with OVs/irinotecan, including HSV-1 encoding CYP2B1,127 reovirus,128 and Sindbis virus 126. However, only the study on Sindbis virus looked at immune components in irinotecan synergy, concluding that natural killer cells are essential for the process 126…”
Section: Combining Chemotherapeutic Drugs With Ov Therapymentioning
confidence: 99%
“…One study showed that application of a Sindbis vector with oncolytic properties in combination with the topoisomerase inhibitor irinotecan in SCID mice bearing human ovarian cancer resulted in prolonged animal survival [33]. The authors highlight the role of natural killer cells in the induction of the anti-cancer effect by the combined treatment.…”
Section: Introductionmentioning
confidence: 99%
“…SV has shown promise as an anticancer agent in several preclinical models (Tseng et al, 2004;Zhang et al, 2004;Saito et al, 2009;Huang et al, 2011;Granot and Meruelo, 2012); however, translation of these findings to use in the clinic could be hindered by its pathology, which manifests as Pogosta disease in humans.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to these properties, SV replicates extremely rapidly, with daughter virions beginning to bud from infected cells within 4 hr of infection . Bearing these properties in mind, we find it unsurprising that SV has shown promise as anticancer agent in several animal models (Tseng et al, 2004;Zhang et al, 2004;Saito et al, 2009;Huang et al, 2011;Granot and Meruelo, 2012) and is being targeted for clinical translation.…”
Section: Introductionmentioning
confidence: 96%